A Control Strategy for Single-phase Grid-Connected Inverter with Power Quality Regulatory Function - Jin Jiapei; Chen Tiantian; Luo Ling; Su Shaoze (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A single-phase grid-connected inverter system based on LCL filter is established，which combines the features of inverter and active power filter. A composite control strategy for grid-connected inverter with the function of implementing reactive power compensation and harmonic compensation in the grid-connected power generation is proposed. Firstly, grid-connected inverter system structure and model is analyzed. A quasi-Proportional Resonant control method to gain the control of grid-connected fundamental wave current containing reactive power compensation current as well as the control of harmonic compensation currents is put forward; then the calculation methods of  composite control command current based on both second order generalized integrator-quadrature signal generator (SOGI-QSG) and instantaneous reactive power theory are given. Finally, the effectiveness of the control strategy proposed in this paper is verified by simulation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3911